Open lung biopsy in children with diffuse lung disease. Issue 1 (January 1974) - Hewitt, C. J.; Hull, D.; Keeling, Jean W.
Abstract : Open lung biopsy is occasionally the only way to diagnose certain diffuse lung disorders in childhood. The clinical histories of 24 children with diffuse lung disease and the histological appearance of material obtained at open lung biopsy are reported, and published reports are reviewed.